Effect of compaction intensity and abscisic acid on growth, turf quality and root development in turfgrass on clay-based surface - Lakshmipathy, M; Prasad, K V; Raju, V S D; Namita; Manjaiah, K M; Niranjan, P H P; Harish, M N; Pavankumar, M (Plant Science Today, 2026)
Soil compaction is a key factor influencing turfgrass performance, especially in cricket pitches where a firm, consistent surface is essential for optimal playability. This study investigated the effect of varying soil compaction level (1.2 g/cc to 1.6 g/cc) on the growth and performance of two Bermuda grass varieties, namely Selection-1 and Tif-419 and evaluated the role of abscisic acid (ABA) in mitigating compaction stress. Among the two, Selection-1 consistently outperformed Tif-419 in terms of turf quality, Normalised difference vegetation index (NDVI) and root growth. Higher compaction (B5: 1.6 g/cc) significantly suppressed shoot and root biomass along with root morphological traits, while lower compaction levels (B1: 1.2 g/cc and B2: 1.3 g/cc) promoted healthier growth. ABA application showed a limited impact on shoot and root development. However, the highest concentration (10 µM) led to a slight decrease in NDVI. Strong positive correlations (> 0.9) were observed between root traits, NDVI and turf quality, underscoring the critical role of root health in turfgrass performance. The findings highlight that excessive compaction adversely affects turf growth and ABA offers minimal benefit under such stress. These findings pave the way for integrated soil management practices to alleviate compaction and enhance the sustainability of turfgrass systems.